2018
DOI: 10.3389/fpls.2018.00659
|View full text |Cite|
|
Sign up to set email alerts
|

Nitric Oxide Affects Rice Root Growth by Regulating Auxin Transport Under Nitrate Supply

Abstract: Nitrogen (N) is a major essential nutrient for plant growth, and rice is an important food crop globally. Although ammonium (NH4+) is the main N source for rice, nitrate (NO3-) is also absorbed and utilized. Rice responds to NO3- supply by changing root morphology. However, the mechanisms of rice root growth and formation under NO3- supply are unclear. Nitric oxide (NO) and auxin are important regulators of root growth and development under NO3- supply. How the interactions between NO and auxin in regulating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 91 publications
3
40
0
Order By: Relevance
“…NO is a gaseous free radical that can easily diffuse through biofilms. NO plays a role in numerous plant physiological processes (Begara-Morales et al, 2019), such as transport (Sun et al, 2018), germination (Liu et al, 2010;Arc et al, 2013a), flowering (Khurana et al, 2011), metabolism (Hasanuzzaman et al, 2018), and senescence (Sun, 2018). Moreover, NO is a significant signaling molecule that regulates the plant response to various nonbiological and biological stresses (Begara-Morales et al, 2018), such as stomatal closure (Zhang et al, 2019), heat stress (Parankusam et al, 2017), disease (Srinivas et al, 2014), drought (Wang et al, 2016), and programmed cell death (Ma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NO is a gaseous free radical that can easily diffuse through biofilms. NO plays a role in numerous plant physiological processes (Begara-Morales et al, 2019), such as transport (Sun et al, 2018), germination (Liu et al, 2010;Arc et al, 2013a), flowering (Khurana et al, 2011), metabolism (Hasanuzzaman et al, 2018), and senescence (Sun, 2018). Moreover, NO is a significant signaling molecule that regulates the plant response to various nonbiological and biological stresses (Begara-Morales et al, 2018), such as stomatal closure (Zhang et al, 2019), heat stress (Parankusam et al, 2017), disease (Srinivas et al, 2014), drought (Wang et al, 2016), and programmed cell death (Ma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that MYC2 mediates JA-induced inhibition of apical root growth by directly suppressing the expression of auxin-responsive PLTs. This also suggested that auxin and its downstream regulators mediate the stress-induced inhibition of root growth, and the hypothesis is supported by an increasing number of studies [52][53][54].…”
Section: Auxin and Root Developmentmentioning
confidence: 77%
“…Auxin stabilizes the communication among TRANSPORT INHIBITOR RESPONSE1/AUXIN SIGNALLING F-BOX proteins (TIR1/AFB3) and Domain II of AUXIN/INDLOE-3-ACETIC ACID (AUX/IAA) transcriptional co-regulators to stimulates the ubiquitin-dependent breakdown of AUX/IAA protein in the 26S proteasome [111] (Figure 2B). When the auxin concentration is low, individuals from the AUXIN/IAA-INDUCIBLE (AUX/IAA) family of transcriptional repressors bind with DNA-binding protein of ARF [112,113], which exactly possess auxin-response promoter elements (AuxREs) in various auxin-regulated genes [114,115]. AUX/IAA protein inhibits the ARF function either by passively sequestering ARF protein away from their specific target promoters [116], or by interacting AUX/IAA with the co-repressor TOPLESS (TPL) to stimulate chromatin inactivation and silencing of ARF target genes [117].…”
Section: Auxin Response Networkmentioning
confidence: 99%
“…Recent studies demonstrated that auxin accumulation in the LRs primordia overlaps with the low nitrate-stimulated expression of TAR2 in the root [16,85]. The application of the 2-4-carboxyphenyl-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) under NO 3 − supply, initiates auxin (IAA) level in the root [112]. In contrast to wild-type (WT), the ospin1b mutant has lower auxin level in their root, fewer LRs and shorter seminal root (SRs).…”
Section: Influence Of Auxin Concentration On Root Growthmentioning
confidence: 99%
See 1 more Smart Citation